Fossil evidence for vampire squid inhabiting oxygen-depleted ocean zones since at least the Oligocene - Martin Košťák; Ján Schlögl; Dirk Fuchs; Katarína Holcová; Natalia Hudáčková; Adam Culka; István Fözy; Adam Tomašových; Rastislav Milovský; Juraj Šurka; Martin Mazuch (Communications Biology, 2021)
A new fossil of a vampire squid bridges a 120 million-year gap in their fossil record. Vampire squid today are adapted to low oxygen, deep sea environments and this new specimen provides evidence that the deep sea specialisation of vampire squid may have been triggered during the development of oxygen minimum zones in the oceans during the Cretaceous and Cenozoic.